Factors Influencing Obstetric Fistula among Women of Childbearing Age at Banadir Hospital, Somalia - Ahmed, Hassan Mohamed (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on the factors influencing obstetric fistula among the women of childbearing age at Banadir hospital, Somalia. The specific objectives of the study include: to identify the factors that contribute to obstetric fistula among women of childbearing age at Banadir Hospital in Somalia, to assess the impact of obstetric fistula on the physical, emotional, and social well-being of affected women at Banadir Hospital in Somalia and to explore potential interventions and strategies to prevent and manage obstetric fistula among women of childbearing age at Banadir Hospital in Somalia. The study also employed quantitative research approach research method to investigate the factors that contribute to obstetric fistula among women of childbearing age at Banadir Hospital in Somalia. The study utilised close-ended questionnaire instrument data collected from the respondents of the study was entered, coded, sorted, organized and analyzed using Statistical Package Software Science (SPSS) version 28. The findings of the study on factors that contribute to obstetric fistula among women of childbearing age at Banadir Hospital in Somalia which they include: lack of access to skilled obstetric care, poverty prevent women from seeking appropriate medical care during pregnancy and childbirth, lack of education, cultural and social factors, lack of access to clean water and sanitation and gender inequality. The impact of obstetric fistula on the physical, emotional, and social well-being of affected women at Banadir Hospital in Somalia include: chronic incontinence leading to foul-smelling leaks of urine and/or feces, which can cause skin irritation and infections, painful sores and ulcers in the genital area, malnutrition and dehydration due to difficulty in eating and drinking, chronic pelvic and abdominal pain, increased risk of reproductive health issues, including infertility and recurrent infections, feelings of shame, guilt, and isolation due to the stigma associated with obstetric fistula, depression, anxiety, and low self-esteem, loss of sense of self-worth and identity and trauma and social exclusion and discrimination from family, friends, and community members. The potential interventions and strategies to prevent and manage obstetric fistula among women of childbearing age at Banadir Hospital in Somalia entail: increasing access to skilled birth attendance by providing more trained healthcare providers, improving access to emergency obstetric care by ensuring that women have access to timely and appropriate medical care during childbirth, promoting family planning and contraception by empowering women to make informed choices about family planning and access to contraception, addressing cultural and social determinants by tackling underlying social norms and cultural practices that may contribute to obstetric fistula.